The effect of education based on health belief model on promoting preventive behaviors of hypertensive disease in staff of the Iran University of Medical Sciences - Nemam Ali Azadi; Arash Ziapour; Javad Yoosefi Lebni; Seyed Fahim Irandoost; Jaffar Abbas; Fakhreddin Chaboksavar (BMC, 2021)
Abstract Background Hypertension is one of the major causes of many diseases, such as heart attack, strokes, kidney failure, and many internal disorders. This presentresearch study aimed to investigate the impact of educational programs based on the health belief model to promote hypertension prevention behavior of Iran University of Medical Sciences staff. Methods This study has incorporated pretest-posttest quasi-experimental based on 128 staff members and randomly assigned the recruited and involved participants to an intervention (n = 64) and a control group (n = 64). The data collection tool was based on a questionnaire related to health belief model constructs based on 42 questions. The study interpreted the results using ANCOVA and robust ANCOVA as suitable approaches. Results ANCOVA showed improvement in the cues to participants' action following educational interventional (p = 0.011). the robust ANCOVA specified that the intervention was successful for participants with low to moderate initial levels of knowledge, perceived susceptibility, perceived severity, perceived barriers, and self-efficacy scores. The levels of these components did not change in participants with very high baseline scores. Compared to a control group, regardless of baseline score, the perceived benefits and practice (behavior) of participants at the intervention group were improved significantly (P <  0.05). Conclusion This current study specified that the education-based health belief model effectively promotes hypertension preventive behaviors among Iran University of Medical Sciences staff.